EKSPLORASI ETNOMATEMATIKA PERMAINAN OGO MASYAKAT ENDE PADA SISWA KELAS VII SMP KRISTEN ENDE - Getrudis Wae; Ariswan Usman Aje; Konstantinus Denny Pareira Meke (Program Studi Pendidikan Matematika, 2022)
Ethnomathematics-based totally gaining knowledge of is very crucial to instill man or woman values while at the equal time fostering kid's love for the local way of life which has been deserted because of technological advances the mathematical standards determined within the ogo game are the ideas of flat aircraft geometry, diversifications, and mathematical logic. (1)The form of the ogo plot contains geometric ideas of flat planes together with squares, rectangles, semi-circles, dice nets, and additionally the idea of mirroring. (2). Ogo sport, judging from the order of the ogo sport, the players start by way of drawing lots by means of doing hompimpa. that is in which there may be the idea of permutations in the ogo game to calculate the sample of the ogo recreation sequence. (3). The policies of the ogo recreation, the concept contained in the policies of the ogo recreation is the idea of mathematical logic visible inside the proper and wrong of a recreation. based totally on the outcomes of the study, the researchers concluded that there are ideas of flat plane geometry at the ogo plot, particularly square, rectangle, and semi-circle. As for different mathematical standards contained in the ogo plot inclusive of mirroring, cube nets, mathematical logic, and diversifications.